2020
DOI: 10.1097/mat.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Veno-venous Extracorporeal Membrane Oxygenation Support in COVID-19 Respiratory Distress Syndrome: Initial Experience

Abstract: SARS-CoV-2 may cause severe respiratory failure due to massive alveolar damage. Currently, no adequate curative therapy for Coronavirus Disease 2019 (COVID-19) disease exists. By considering overall impact of COVID-19 pandemic outbreak, an increased need of extracorporeal membrane oxygenation (ECMO) support becomes evident. We report on our preliminary institutional experience with COVID-19 patients receiving venovenous ECMO support. ASAIO Journal XXX; XX:00-00.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
(56 reference statements)
3
12
0
7
Order By: Relevance
“…A total of 102 articles were retrieved from the database search and snowballing. Following the exclusion of duplicates and screening, a total of 25 articles were selected for inclusion in this systematic review 6‐30 (Figure 1). The characteristics of these studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 102 articles were retrieved from the database search and snowballing. Following the exclusion of duplicates and screening, a total of 25 articles were selected for inclusion in this systematic review 6‐30 (Figure 1). The characteristics of these studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Loforte et al 15 also reported that three out of four patients were weaned off ECMO, and although a 75% weaning rate appears successful, one of the three weaned patients eventually died after VV‐ECMO removal. The final patient died due to severe gastrointestinal bleeding while on ECMO, highlighting the potentially fatal complications associated with ECMO (with bleeding being the most frequent) 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate research study by Loforte et al., 75% weaning rate was reported; however,one- third of weaned patients died after subsequent VV-ECMO removal. 17 Also, the remaining patient of the four had severe gastrointestinal bleeding while on ECMO, a severe complication linked to ECMO. 18 Thus, with a final mortality rate of 50%, with 2 out of 4 patients eventually dying, these results were also inconclusive in terms of the benefit of ECMO in COVID-19.…”
mentioning
confidence: 99%
“… 15 China Case series 16 (8) N/A 7 on VV-ECMO 1 on VA-ECMO N/A Loforte et al. 17 Italy Observational 59 (4) 59 VV-ECMO used in all patients 1 (25) Marullo et al. 16 Europe Retrospective 333 (333) N/A VV-ECMO used in 93.7% of cases 57 (17.1) Nakamura et al.…”
mentioning
confidence: 99%